Correlation between functional properties and structural properties of flexible pavement - Nurzahrin Mohmad Barudin, author; Haryati Yaacob, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017